Sosialisasi dan Pelatihan Pembuatan Paving Block dengan Pemanfaatan Sampah Plastik di Posyantek Alamanda 28 Kota Bekasi - Dicki Dian Purnama; Bahar Amal; Arnisa Stefanie; Lela Nurpulaela; Dika Nur Kholish; Dimas Bayu AS; Syuraih Amiruddin; Dika Satria; Fajar Eka Subagja (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The community service program focuses on solving environmental problems, especially plastic waste management. This program will provide training and socialization on the technology used to make paving blocks made from a mixture of plastic. With the increasing amount of plastic waste, a creative approach is needed to recycle it and turn it into a useful product. At Posyantek 28 Alamanda, Bekasi City, the community was given training on making paving blocks from a mixture of plastic waste according to SNI 03-0691-1996. The results of the activity showed that the training participants understood the material better and were able to make paving blocks from plastic waste, which produced products that met technical standards. Through its efforts to increase community participation in recycling plastic waste, this program is expected to create new economic opportunities